Effect of Aureomycin®, injectable Tramisol® and Ectrin® fly control ear tags on grazing steer performance - Corah, L.; O'Neill, S.; Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station, 2011)
Steers consuming a free choice mineral mix containing Aureomycin (437 mg per hd per day) gained 15.3% faster than controls during a 129 day grazing trial on brome grass pasture. There was considerable variation in daily mineral intake and daily Aureomycin consumption among the 12 pasture replicates. Worming the locally produced steers with Tramisol resulted in a small but non-significant improvement in gain. Two Ectrin fly control ear tags per steer (three pastures within each mineral treatment for the final 61 days of the trial) resulted in a 0.25 lb daily gain increase. Average horn fly counts for tagged steers was <1 vs. 60 for non-tagged steers.
Keywords: Beef; Fly tags; Performance; Steer